From a stratigraphic sequence to a landscape evolution model: Late Pleistocene and Holocene volcanism, soil formation and land use in the shade of Mount Vesuvius (Italy). (11th February 2016) - Vogel, Sebastian; Märker, Michael; Rellini, Ivano; Hoelzmann, Philipp; Wulf, Sabine; Robinson, Mark; Steinhübel, Linda; Di Maio, Giovanni; Imperatore, Catello; Kastenmeier, Pia; Liebmann, Liana; Esposito, Domenico; et al.
Abstract: Detailed lithostratigraphic, geochemical, pedological, micromorphological and archaeological analyses were carried out at a stratigraphic sequence of Scafati, about 3 km east of ancient Pompeii. It comprises roughly the last 22, 000 years of landscape history consisting of a multilayered succession of repeated volcanic deposition and pedogenesis. The former is caused by several phases of volcanic activity of Somma-Vesuvius, Campi Flegrei and Ischia, reflecting a large spectrum of eruption types including Plinian, sub-Plinian, Strombolian to Vulcanian and effusive volcanic events. The latter contains phases of volcanic quiescence leading to soil formations of different durations, intensities and soil-forming environments. Furthermore, the paleosols repeatedly reveal clear evidence of anthropogenic activity such as agriculture. Using this multiproxy approach, a holistic landscape evolution model was developed reconstructing the late Pleistocene and Holocene history of volcanic activity, soil formation and land use in the hinterland of Pompeii. This was correlated with the larger-scale climatic and human history of the Campania region.